The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1021/ma501125k
|View full text |Cite
|
Sign up to set email alerts
|

Air Stable and Latent Single-Component Curing of Epoxy/Anhydride Resins Catalyzed by Thermally Liberated N-Heterocyclic Carbenes

Abstract: Bisphenol A diglycidyl ether (BADGE) is cured thermally using phthalic acid anhydride (PhA) or hexahydrophthalic anhydride (HHPA) as hardener in the presence of different protected N-heterocyclic carbenes (NHCs), from which the catalytically active NHCs are generated in situ upon heating. It is found that the curing reactions proceed in a well-defined manner, delivering highly cross-linked, high-T g-thermosets using low catalyst loadings (0.1–1 mol % of NHC precursor). The polymerizations can be conducted unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Epoxides have recently also been copolymerized with anhydrides, using thermally generated NHCs as curing agents . Bisphenol A diglycidylether (BADGE) and hexahydrophthalic anhydride (HHPA) were converted this way to duroplastic material, importantly without the need for protective reaction conditions.…”
Section: Ring‐opening Polymerizationsmentioning
confidence: 99%
“…Epoxides have recently also been copolymerized with anhydrides, using thermally generated NHCs as curing agents . Bisphenol A diglycidylether (BADGE) and hexahydrophthalic anhydride (HHPA) were converted this way to duroplastic material, importantly without the need for protective reaction conditions.…”
Section: Ring‐opening Polymerizationsmentioning
confidence: 99%
“…These catalysts can initiate polymerization under external impetus such as thermal or photo irradiation. Various kinds of latent catalysts are used in the polymerization reaction such as sulfonium salt [1][2][3][4], phosphonium salt [5], pyrazinium salt [6], N-heterocyclic carbene [7], aminimide [8], and sulfonate [9]. We have previously reported that primary alkylamines intercalated with α-zirconium phosphate (α-ZrP) can serve as latent thermal initiators in the reaction of glycidyl phenyl ether (GPE) [10] and that intercalation compounds of 1,4-diazabicyclo(2,2,2)octane (DABCO) and 1,8-diazabicyclo(5,4,0)undec-7-ene (DBU) with α-ZrP: α-ZrP·DABCO and α-ZrP·DBU show good performance as latent thermal catalysts in the reaction of GPE with hexahydro-4-methylphthalic anhydride (MHHPA) [11].…”
Section: Introductionmentioning
confidence: 99%
“…[ 10,16,19,20 ] For the synthesis of poly(ε-caprolactam) and poly(ε-caprolactam)-co -poly(lauryllactam) by the action of protected NHCs and their properties, refer to refs. [9 , 13] To obtain melt spun poly-LL-co -poly-ε-CL fi bers, 3 g (75 wt%) of CL, 1 g (25 wt%) of LL, and 5 wt% of 6-Cy-CO 2 were mixed in a mortar inside a glove box.…”
Section: Methodsmentioning
confidence: 99%